Proposal of a Data Warehouse for Scholarly Institutions built on Institutional Repositories - de Albuquerque, Pablo César (2021)
A Data Warehouse (DW) is a tool that integrates and unifies information from multiple data sources and is used to assist decision making. In academic institutions, a Data Warehouse oriented to scientific and academic intellectual production could provide valuable information to understand, optimize and promote the processes involved in intellectual production. This work proposes to use the data sources that conform the Institutional Repositories to start developing a DW.